2011
DOI: 10.1002/xrs.1350
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of EUV periodic multilayers

Abstract: Nanometric Co/Mg, Co/Mg/B 4 C, Al/SiC and Al/Mo/SiC periodic multilayers deposited by magnetron sputtering are studied in order to correlate their optical performances in the extreme ultraviolet (EUV) range to their structural quality. To that purpose, our recently developed methodology based on high resolution x-ray emission spectroscopy (XES) and x-ray and EUV reflectometry is now extended to nuclear magnetic resonance (NMR) spectroscopy and time-of-flight secondary ions mass spectrometry (ToF-SIMS). The ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The Mo valence states have not been studied since the corresponding emission (Mo Lβ 2 , 4d -2p 3/2 transition), accessible with our spectrometer, is not very sensitive to the chemical state of the molybdenum atoms. The same is true with the Co atoms [27].…”
Section: X-ray Emission Spectroscopymentioning
confidence: 54%
“…The Mo valence states have not been studied since the corresponding emission (Mo Lβ 2 , 4d -2p 3/2 transition), accessible with our spectrometer, is not very sensitive to the chemical state of the molybdenum atoms. The same is true with the Co atoms [27].…”
Section: X-ray Emission Spectroscopymentioning
confidence: 54%
“…The studied superlattice has the following structure and aimed thicknesses: x-ray optical applications, has already been characterized [21,22]. From measurements of reflectivity in the hard x-ray and extreme UV regions, of soft x-ray magnetic resonant reflectivity, and of x-ray emission and nuclear magnetic resonance spectroscopies, it was found that the interfaces were abrupt.…”
Section: Experimental and Simulation Detailsmentioning
confidence: 99%
“…This kind of methodology has been already used successfully for the study of nanometer periodic multilayers designed for x--ray optics, see Refs. [2][3][4][5][6] for example.…”
Section: Introductionmentioning
confidence: 99%